A case of superficial CD34 positive fibroblastic tumor: Diagnostic challenges and pitfalls - Soumya Dey; Uttara Chatterjee (Wolters Kluwer Medknow Publications, 2024)
Superficial CD34 positive fibroblastic tumor (SCPFT) is a recently described soft tissue tumor of intermediate grade with predilection for subcutaneous and superficial fascial planes. Morphological diagnosis of these tumors can be challenging because of overlapping features with other benign and malignant soft tissue tumors of fibroblastic and myofibroblastic origin. A middle-aged man came with a subcutaneous mass in the left thigh. Microscopic examination showed features of an SCPFT comprised of a circumscribed spindle cell tumor with focal striking pleomorphism and bizarre hyperchromatic nuclei. Immunohistochemically (IHC), the tumor cells showed diffuse positivity for CD34 and focally for cytokeratin. Diagnosis of SCPFT on the basis of morphology alone can be challenging. A constellation of clinicoradiological profiles, IHC features, and sometimes molecular studies clinch the definitive diagnosis which can be helpful in avoiding overtreatment and chemotherapy. Here we highlight the diagnostic challenges and pitfalls in a case of SCPFT.